Islamic Guiding Principles for Sustainable Development A Case Study of International Islamic School (IIS), IIUM (Prinsip Panduan Islam bagi Pembangunan Berkekalan Kes Kajian International Islamic School (IIS), UIAM) - Amanullah, Muhammad (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
Abstract Sustainable development is a term that signifies development for the well-being of both present and future generations of humans. It has become universal concern of all the modern nations. Yet, a set of comprehensive conditions or guiding principles for sustainable development is yet to be devised. Islam has guiding principles of sustainable development. By analysing the related Qur’anic verses and Prophetic ahadith, this paper intends to develop a set of comprehensive guiding principles of sustainable development so as to make them beneficial for governments and organizations which really want to maintain sustainable development for both present and future generations. This study, in addition, intends to conduct a survey to determine whether the complex of International Islamic School (IIS) under International Islamic University Malaysia (IIUM) fulfils these principles or not. This paper concludes that in Islam sustainable development requires balance between present and future life; and between worldly life and life hereafter. Keywords: Sustainable Development, Present, Future, Islamic Guiding Principles, IIS. Abstrak Pembangunan berkekalan adalah istilah yang melambangkan pembangunan untuk kesejahteraan kedua-dua generasi manusia masa kini dan masa depan. Ia menjadi masalah bagi semua bangsa moden. Namun, syarat berkomprehensif atau prinsip panduan bagi pembangunan berkekalan masih belum dicipta. Islam mengandungi prinsip panduan pembangunan berkekalan. Dengan menganalisis ayat-ayat al-Quran yang terkait dan hadis-hadis Rasul (saw), kajian ini bertujuan untuk membentuk satu set prinsip panduan yang lengkap untuk pembangunan berkekalan supaya ia bermanfaat kepada kerajaan dan organisasi yang benar-benar mahu mengekalkan pembangunan yang berkekalan untuk kedua-dua generasi masa kini dan masa depan. Disamping itu, kajian ini bertujuan untuk menjalankan kajian bagi menentukan sama ada International Islamic School (IIS) di bawah Universiti Islam Antarabangsa Malaysia (UIAM) memenuhi prinsip-prinsip ini atau tidak. Kajian ini menyimpulkan bahawa pembangunan berkekalan dalam Islam memerlukan keseimbangan kehidupan antara masa kini dan masa depan; dan antara kehidupan dunia dan kehidupan akhirat. Kata Kunci: Pembangunan Berkekalan, Masa Ini, Masa Depan, Prinsip Panduan Islam, IIS.